Relationship between triglyceride–glucose index and carotid plaques in a high-stroke-risk population in southeast china: A population-based cross-sectional survey - Tang, Xiang; Zhang, Lulu; Li, Yidan; Zhou, Yun; Cai, Xiuying; Yao, Ye; Fang, Qi (Frontiers in Endocrinology, 2022)
Background: Cervical arterial atherosclerosis (CAA) is an important risk factor of stroke in China. The triglyceride-glucose (TyG) index is a simple and low cost marker for ischemic stroke. Whether the TyG index predicts cervical arterial atherosclerosis remains uncertain. This study aimed to investigate the relationship between TyG index and cervical arterial atherosclerosis. Methods: This cross-sectional study was conducted in the residents aged ≥40 in the general population of Southeast China. All participants completed a detailed questionnaire and provided blood samples. The high-stroke-risk groups further complete cervical artery ultrasonography. TyG index was calculated by a well-established formula and analyzed by quartiles (Q1-Q4). Multivariate logistic regression was used to investigate the relationship between TyG index and cervical arterial atherosclerosis. Results: A total of 4499 people aged ≥40 years were finally included, among whom 23.47% are high-stroke-risk population. The prevalence of increased intima media thickness (IMT), carotid plaque, and cervical artery stenosis (CAS) in the high-stroke-risk population were 21.97%, 39.3%, and 6.1%, respectively. Subjects with higher TyG were still more likely to have carotid plaque. After adjusting for several established risk factors, compared with the TyG-Q1 group, the TyG -Q2, TyG -Q3, and TyG -Q4 groups were more likely to have carotid plaque (OR 1.85, CI 1.28-2.67; OR 1.51, CI 1.05-2.18; OR 1.29, CI 0.90-1.84). TyG was an independent predictor of the presence of plaque in the carotid artery of the high-stroke-risk population. Conclusions: Elevated TyG index is a potential predictor for carotid plaques in high-risk population for stroke that is older than 40 years.